2019
DOI: 10.1093/neuonc/noz089
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale drug screen identifies selective inhibitors of class I HDACs as a potential therapeutic option for SHH medulloblastoma

Abstract: Background Medulloblastoma (MB) is one of the most frequent malignant brain tumors of children, and a large set of these tumors is characterized by aberrant activation of the sonic hedgehog (SHH) pathway. While some tumors initially respond to inhibition of the SHH pathway component Smoothened (SMO), tumors ultimately recur due to downstream resistance mechanisms, indicating a need for novel therapeutic options. Methods Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…Based on the mechanism, we hypothesize the synergistic beneficial effects of ubenimex and the pan HDAC inhibitor Quisinostat, which was reported to inhibit cancer cells self-renewal and the growth of medulloblastoma. 33,34 Tumor cells and xenografts exposed to the combination therapy show inhibited cellular proliferation characterized by lower levels of Cyclin A and D1. It is important to note that the combination therapy is also synergistic in the HCC metastatic PDX models, indicating that the novel combination treatment is not only effective in primary tumor but also metastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the mechanism, we hypothesize the synergistic beneficial effects of ubenimex and the pan HDAC inhibitor Quisinostat, which was reported to inhibit cancer cells self-renewal and the growth of medulloblastoma. 33,34 Tumor cells and xenografts exposed to the combination therapy show inhibited cellular proliferation characterized by lower levels of Cyclin A and D1. It is important to note that the combination therapy is also synergistic in the HCC metastatic PDX models, indicating that the novel combination treatment is not only effective in primary tumor but also metastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…HDACis show more pronounced effects on proliferation of SHH-driven MB cells harboring a mutation in the gene encoding for the histone acetyltransferase (HAT) CREBBP, when compared to CREBBP wild-type controls (Hellwig et al, 2019). A targeted small-molecule screen on the stable, SHH-dependent murine MB cell line SMB21 reveals selective inhibitors of class I HDACs as promising antitumor agents for SHH MB, and the novel class I HDAC inhibitor JNJ-26481585 (quisinostat) consistently inhibits growth of SHH MB in vivo as well as in vitro (Pak et al, 2019). Another recent study using a high-throughput cell viability assay to screen 12,800 compounds identified two HDACis, JNJ-26481585 and dacinostat, as anti-proliferative agents in MB.…”
Section: Medulloblastomamentioning
confidence: 99%
“…SMO-inhibitor vismodegib blocks Hedgehog pathway which regulates the skin growth. In case of medulloblastoma, HDAC inhibitors are active against even SMO-inhibitor resistant cell lines 37 . Hence, concurrent use of HDAC- and SMO- inhibitors holds a promising strategy to target melanoma, as predicted by romidepsin and vismodegib combination (Fig.…”
Section: Discussionmentioning
confidence: 99%